Using Bran of Ancient and Old Grains for Wheat Bread Production - Oumayma Toumi; Costantino Fadda; Alessandra Del Caro; Paola Conte (Foods)
In the current era of heightened awareness regarding the impact of food choices, there has been a noticeable shift towards revisiting traditional ingredients. Following the growing interest in ancient grains, this study evaluated their potential use for enriching modern wheat dough and bread. The effects of substituting 20% of wheat flour with the bran of seven ancient grains on dough’s rheological properties and bread quality were assessed. The bran-enriched doughs maintained high stability (ST) values and showed an enhanced elastic behavior compared to the control. Nonetheless, a reduction in dough extensibility (E) was also noted. In terms of bread measurements, all bran-enriched breads exhibited a lower specific volume and a darker crust and crumb compared to the control bread. However, not all of the bran breads showed a harder and chewier loaf texture. The composite breads also exhibited enhanced total dietary fiber (TDF) and polyphenol content. A sensory evaluation revealed that Garfagnana (GAR) and Norberto (NOR) bran-breads received the highest overall liking scores. In conclusion, the incorporation of ancient grain brans presents a promising approach to enhancing modern wheat doughs and breads, offering nutritional benefits without significantly compromising their sensory and textural properties.